Сучасні формації розвитку підприємств альтернативної енергетики: акцент на біопаливо - Климчук, М. М. (Ways to Improve Construction Efficiency, 2014)
The presented scientific articles identified determinants of effectiveness and efficiency of the functioning of alternative energy companies. The author singles out the problems of alternative energy companies and provided recommendations for possible solutions. The basic steps to support the development of alternative energy companies to carry through the prism of complex-system approach in the context of the implementation of strategic goals of the state: energy efficiency and energy independence.